A nonlinear model for ski boot hysteresis - Eberle, R.; Kaps, P.; Heinrich, D.; Mössner, M.; Hofer, P.; Schindelwig, K.; Nachbauer, W. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
For the simulation of skiing one needs a moment-angle relation for the ski boot in the ankle joint. This relation shows a hysteresis. For this one has to consider the stiffness of the boot shell, but also the plasticity of the ski boot liner and the soft tissue of the shank. As a first approach a linear fit for the hysteresis loop was used in. Here, the relation is improved by a nonlinear fit. The measurement and modeling are treated in this work.